2014
DOI: 10.1177/0333102414527016
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in the brain of hemiplegic migraine patients measured with 7 tesla 1H-MRS

Abstract: We found a decreased cerebellar tNAA/tCre ratio that might serve as an early biomarker for neuronal dysfunction and/or loss. This is the first high-spectral resolution 7 tesla (1)H-MRS study of interictal biochemical brain changes in hemiplegic migraine patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Contrary to earlier some clinical reports from the interictal period (6, 12, 40, 62), the present findings do not display a significant deviation in the trend attributed to NAA, and the levels remained relatively consistent in the NTG versus saline injected rats, which is more in line with the majority of clinical 1 H MRS migraine studies (16). NAA is widely held as a marker for neuronal and axonal integrity and is indicative of mitochondrial functioning as it is synthesized in neural mitochondria (12, 62). Physiologically, the changes in NAA seen in migraine and consequent mitochondrial disruption could be a result of long-term or repeated migraine.…”
Section: Discussioncontrasting
confidence: 54%
“…Contrary to earlier some clinical reports from the interictal period (6, 12, 40, 62), the present findings do not display a significant deviation in the trend attributed to NAA, and the levels remained relatively consistent in the NTG versus saline injected rats, which is more in line with the majority of clinical 1 H MRS migraine studies (16). NAA is widely held as a marker for neuronal and axonal integrity and is indicative of mitochondrial functioning as it is synthesized in neural mitochondria (12, 62). Physiologically, the changes in NAA seen in migraine and consequent mitochondrial disruption could be a result of long-term or repeated migraine.…”
Section: Discussioncontrasting
confidence: 54%
“…This relationship between a migraine and decrease cerebellum volume leads to cognitive and motor function loss over time. Zielman et al stated that a migraine caused atrophy in the brain and led to cerebellar neural damage [12]. In migraine patients, vestibulocochlear dysfunction and balance problems often arise because of neuronal loss in the cerebellum [13].…”
Section: Discussionmentioning
confidence: 99%
“…Creatine provides a measure of energy stores. A single case study is not convincing to argue that this is typical of pediatric migraineurs, although several studies of migraine in adults have shown decreased NAA in various regions of the brain; [99][100][101][102][103] one study observed an increase in NAA in the pons in episodic migraineurs, 104 and many studies have not observed any differences in NAA levels in various regions of the brain. 84,85,97,[105][106][107][108][109][110][111][112][113][114] Location, in addition to type of migraine, and migraine severity may also confound results and explain some of these discrepancies.…”
Section: Metabolitesmentioning
confidence: 99%